Effects of Posttraumatic Stress Disorder Status and Covert Hostility on Cardiovascular Responses to Relived Anger in Women with and without PTSD - Vrana, Scott R. (2009)
Previous literature has found greater heart rate (HR) and blood pressure (BP) responses during relived anger, and a positive association between covert hostility and relived anger, in male veterans with PTSD. This study investigated hostility and cardiovascular responses to a relived anger task in 120 women (70 with PTSD and 50 without PTSD). Women with PTSD reported greater hostile beliefs and covert hostility than non-PTSD controls, reported greater anger and anxiety during the anger recall task, and had higher resting HR. In general, the relationship between PTSD and cardiovascular response was moderated by covert hostility, which was associated with greater baseline diastolic BP and greater HR during relived anger and anger recovery among women with PTSD, but not among non-PTSD controls. Results suggest that the relationship between PTSD and cardiovascular response is moderated by hostility.